THE INFLUENCE OF DISCOUNTS AND LIFESTYLE ON IMPULSE BUYING (CASE STUDY OF SHOPEE APP USERS AMONG STUDENTS OF THE FACULTY OF ECONOMICS AND BUSINESS, UNIVERSITAS MALIKUSSALEH) - Erni Fhonna; Munandar; Adnan; T. Edyansyah (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to analyze the influence of discounts and lifestyle on impulse buying (a case study of Shopee users among students at the Faculty of Economics and Business, Universitas Malikussaleh). The study employs a quantitative method, with the population consisting of students from the Faculty of Economics and Business at Universitas Malikussaleh who use Shopee. The sampling method used in this research is stratified random sampling, with 100 respondents. The instrument for measuring responses is based on a Likert scale, and primary data is collected through questionnaires distributed directly to the respondents. The data in this research is analyzed using multiple linear regression analysis, instrument testing, classical assumption tests, hypothesis testing, and the determination coefficient, all processed using SPSS version 27. The results show that discounts do not have a positive or significant effect on impulse buying, as evidenced by a t-value < t-table (-0.708 < 1.664) and a significance value of 0.480 > 0.05. On the other hand, lifestyle has a positive and significant effect on impulse buying, as demonstrated by a t-value > t-table (7.027 > 1.664) with a significance value of 0.000 < 0.05. This research implies that Shopee should emphasize strategies to enhance its marketing efforts, attract consumers, and encourage impulse buying.